Optimal High-Order Method of Moment combined with NURBS for the scattering by a 2D cylinder. - Khairi, R.; Coatanhay, A.; Khenchaf, A. (Advanced Electromagnetics, 2013)
This paper deals with the High-Order Method of Moments (HO-MoM) combined with Non-Uniform Rational Basis Splines (NURBS) segments to evaluate the scattering by a 2D cylinder. The authors mainly focus upon the influence of the different parameters (polynomial basis, order, mesh length, curvature, polarization,...) and try to determine if a optimal choice exists or not for the convergence speed.